Body Consciousness : A Philosophy of Mindfulness and Somaesthetics - Shusterman, Richard (Cambridge University Press, 2013)
Contemporary culture increasingly suffers from problems of attention, overstimulation, and stress. We are further plagued by a growing variety of personal and social discontents generated by deceptive body images. This book argues that improved body consciousness can help relieve these problems and enhance one’s knowledge, performance, and pleasure. If body consciousness is a topic unlikely to comfort conventional philosophical tastes, this is not because philosophy has always ignored the body, as too many somatic advocates are fond of complaining. The body in fact exerts a very powerful (though generally negative) presence in philosophy’s persistent privileging of mind and spirit. Its dominantly negative image – as a prison, distraction, source of error and corruption – is both reflected and reinforced by the idealistic bias and disregard for somatic cultivation that Western philosophers generally display.